An analysis of the Russian post-Soviet modernization process - Karaman, Cem (My University, 2003)
Bu tezin amacı, Sovyetler Birliği'nin yıkılmasından sonra Rusya'nın içine girmiş olduğu sosyal transformasyon sürecini bir modernleşme terimi vasıtasıyla incelemek ve bu süreç hakkında bir anlayış ortaya koymaktır. Bu çabasında, tez özellikle Rusya'nın modernleşme sürecinin ekonomik ve politik yönlerini Rusya'nın Sovyet sonrası ilk on yılını ele alarak incelemektedir. Tez, dört bölümden oluşmaktadır. alışmanın teorik çerçevesini kurmaya çalışmaktadır. Bu bölümde, önce modernleşme teriminin farklı tanımlamaları kısaca sunulmakta daha sonra genel ve modife edilmiş modernleşme teorilerinin genel duruşları ayrıntılı biçimde yansıtılmaktadır.İkinci bölüm, önce Sovyet ekonomik sisteminin belli başlı özellikleri ve son Sovyet lideri Mikhail Gorbaçov'un ekonomik reformlarını anlatmakta, daha sonra Rusya'nın Sovyet sonrası ekonomik reform sürecini detaylı biçimde yansıtmaktadır. Üçüncü bölüm, önce Sovyet politik sisteminin belli başlı özellikleri ve son Sovyet lideri Mikhail Gorbaçov'un politik reformlarını yansıtmakta, daha sonra Rusya'nın Sovyet sonrası politik reform süreci detaylı biçimde anlatmaktadır. Dördüncü bölüm, Rusya'nın Sovyet sonrası transformasyonun ilk on yılı sonunda ortaya çıkan ekonomik ve politik sisteminin farklı unsurlarını detaylı biçimde değerlendirmektedir. Bu çalışma Rusya'nın Sovyet sonrası modernleşmesi en doğru biçimde nasıl anlaşılır sorusunu araştırma problemi olarak benimsemiştir. Çalışmanın bu soruya istinaden vardığı sonuç, Rusya'nın Sovyet sonrası modernleşmesinin farklı bir modernleşme süreci olduğudur. Çünkü, Rusya'nın Sovyet sonrası modernleşmesi, Batı toplumlarında cereyan etmiş alttan gelen ve modern toplum idealine oldukça yakınlaşan gerçek anlamdaki modernleşme sürecinin aksine, yönetici elitlerin tam bir modernleşme felsefesi olmadan devlet aygıtını kullanarak yukarıdan empoze etmeye çalıştıkları ve nihai olarak modern toplum idealine yürümeyen farklı bir süreç olmuştur. This study of An Analysis of The Russian Post-Soviet Modernization Process is on how the Russian post-Soviet modernization can be perceived in true sense. In this respect, this study using the term modernization aims to provide an understanding on Russia's post-Soviet modernization effort and it mainly focuses the economic and political aspects of Russia's modernization process within its first post-Soviet decade. The thesis is composed of four chapters, the first one of which tries to construct theoretical framework of this study. It gives many definitions of the concept modernizationin briefly and describes the key points and assumptions of both general theory of modernization and modified theory of modernization in detailed manner. The following two chapters tries to take photographs of economic and political reform policies executed by Russian reformers in the name of modernization. The second chapter mainly describes Russia's post-Soviet economic reform process under Boris Yeltsin's and Vladimir Putin's presidency. In this respect, it first describes the Soviet economic system's characteristics and as the last Soviet reformist leader, Mikhail Gorbachev's economic reforms, and later describes the economic reform policies under the jurisdiction of both Russian presidents thoroughly. The third chapter of this thesis outlines Russia's post-Soviet political reform process under both presidents' rule. It first reflects the Soviet political system's characteristics and as the last Soviet reformist leader, Mikhail Gorbachev's political reforms, and then describes the elements of Russia's post-Soviet political reform process in detailed manner. The fourth chapter of this thesis tries to analyze the features of Russia's emerging post-Soviet economic and political systems. It evaluates both economic and political distinctive features emerged in Russia's post-Soviet transformation process in detailed manner. At the end, in regarding the question of how Russia's post-Soviet modernization can be perceived in true sense as the main research problem, this study assumes that Russia's post-Soviet modernization is distinctive type of modernization because in contrast to a from below nature of real modernization process in Western societies in which this process reached or came close to modern society, Russia's post-Soviet modernization is state-led and top-down modernization process in which Russia without a real direction caught halfway between modern society and its locality.
Keywords: Siyasal bilimler (Siyaset bilimi); Sovyetler Birliği_Dış İlişkiler; Toplum bilimleri; Uluslararası ilişkiler